2015
DOI: 10.1117/1.jei.24.4.043003
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral imaging applied to demolition waste recycling: innovative approach for product quality control

Abstract: Abstract. Hyperspectral imaging (HSI) based sensing devices were utilized to develop nondestructive, rapid, and low cost analytical strategies finalized to detect and characterize materials constituting demolition waste. In detail, HSI was applied for quality control of high-grade recycled aggregates obtained from end-of-life concrete. The described HSI quality control approach is based on the utilization of a platform working in the near-infrared range (1000-1700 nm). The acquired hyperspectral images were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…TQM approaches are therefore considered in maintaining the quality of RLSC to provide value-added and custom-oriented products (Nikolaidis, 2012;Das and Chowdhury, 2012). However, Serranti et al (2015) stated that QC and QA should be initiated with identified quality parameters when building dismantling and salvaging, to overcome the significant knowledge gaps.…”
Section: Quality Conceptmentioning
confidence: 99%
“…TQM approaches are therefore considered in maintaining the quality of RLSC to provide value-added and custom-oriented products (Nikolaidis, 2012;Das and Chowdhury, 2012). However, Serranti et al (2015) stated that QC and QA should be initiated with identified quality parameters when building dismantling and salvaging, to overcome the significant knowledge gaps.…”
Section: Quality Conceptmentioning
confidence: 99%
“…In recent years, the use of NIR-HSI has grown rapidly in many sectors, including the solid waste sector . In literature, different HSI-based approaches are proposed for plastic recycling (Ulrici et al, 2013;Bonifazi et al, 2015), construction and demolition waste recycling (Palmieri et al, 2014;Serranti et al, 2015;Bonifazi et al, 2015;Bonifazi et al, 2017;Bonifazi et al, 2018c) and WEEE recycling (Palmieri et al, 2014;Bonifazi et al 2018b).…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…The white image (W) is acquired by adopting a standard white ceramic tile under the same conditions as the raw image. Then, image correction is performed by [12],…”
Section: Basic Data Normalizationmentioning
confidence: 99%